Analysis of health care system - resources and nursing sector in Saudi Arabia - Al-Homayan, Abdullah Mohammad; Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan; Islam, Rabiul (AENSI Journals, 2013)
During the last decade, the Kingdom of Saudi Arabia has achieved remarkable success with regards to its healthcare development. Knowing that understanding the economic progress and the health of the nation generally comes hand in hand, the Saudi Government has showered the health care system with serious considerable attention such as increasing the health care budget.To meet the objective, the present study was conducted among nurses of public hospitals in Saudi Arabia. The reason for the examination of the nurses’ performance working specifically in Saudi Arabia lies in the fact that nurses comprise the largest human resource element in healthcare organizations, and thus they have a huge impact on the quality of care and patient outcomes.Despite the efforts being carried out by the Saudi government in developing and enhancing the health sector, there are performance issues particularly with respect to efficient and effective services that are still plaguing the nursing sector specifically and the healthcare industry generally. There is particularly a growing concern about the poor performance of nursing services in Saudi Arabia’s public health sector. In terms of theory, the study contributes to the body of knowledge through the examination of the determinants of hospital nurses’ performance based on an individual’s perspective, and the influence of both the mediation of job stress, and the moderation effect of organizational support in mitigating job stress.